SOCIAL SUKUK FOR SUSTAINABLE DEVELOPMENT –REVIEW OF SUKUK PRIHATIN, IHSAN SUKUK (MALAYSIA) AND CASH WAQF LINKED SUKUK (INDONESIA) - Mustapha, Zakariya; Kunhibava, Sherin; Muneeza, Aishath; Khalid, Maryam; Ming Sen , Thong (I-iECONS e-proceedings, 2023)
Social sukuk are instruments aimed at providing assistance and relief to societies and communities affected by difficulties. For example Sukuk Prihatin was issued with the objective of easing the burden of those affected by Covid-19 Pandemic, Ihsan Sukuk was the first programme approved under the Securities Commission Malaysia Sustainable and Responsible Investment (SRI) Sukuk Framework while the Cash Waqf Linked Sukuk (CWLS) was issued to use waqf funds for building amenities for the community and for other social benefits. The objective of social sukuk is unlike conventional sukuk, where return on investment is the main priority. In a social sukuk the main objective is to enable under-privileged segments of the society to benefit from the funds provided through the issuance of the sukuk. The objective of this research is to explore and understand social sukuk through case studies by examining issues associated with structure and issuance of social sukuk and provide recommendations for future social sukuk issuances. The methodology used in this research is non-doctrinal and document analysis. Secondary sources were reviewed to answer the research objective. This paper examines three case studies, namely the Sukuk Prihatin and Ihsan Sukuk issued in Malaysia and the CWLS in Indonesia. The objectives of these sukuk and their outcomes were examined and compared. Recommendations on future social sukuk structure and issuance are made accordingly.